Предмет: Алгебра,
автор: dimakolchin2003
упростите : а) (3x+1)*(x-4)+(2x-7)*(x+2) б) (4а-2x)*(3a+x)-(6a-x)*(2a+2x)
Ответы
Автор ответа:
0
А) 3x^2-12x+x-4+2x^2+4x-7x-14=-18+5x^2-14x
Автор ответа:
0
a) 3x^2-12x+x-4+2x^2+4x-7x-14=5x^2-18x-18
б) 12a^2+4ax-6ax-2x^2-12a^2+12ax-2ax-2x^2=
= 8ax-4x^2
б) 12a^2+4ax-6ax-2x^2-12a^2+12ax-2ax-2x^2=
= 8ax-4x^2
Похожие вопросы
Предмет: Математика,
автор: aer23serdent
Предмет: Английский язык,
автор: marinamamucogly2
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Физика,
автор: kronaldo
Предмет: Математика,
автор: varkvasovaoxan